Pengaruh Model Pembelajaran Portofolio terhadap Hasil Belajar Siswa Kelas Lima Sekolah Dasar Negeri 101788 Marindal 1 - Putri, Nizmi (Medan Resource Center, 2025)
This study investigates the effect of the Portfolio Learning Model on the learning outcomes of fifth-grade students at SDN 101788 Marindal 1 during the 2024–2025 academic year. The research employed a quasi-experimental design, involving two groups: Class V-A as the control group and Class V-B as the experimental group. Data were collected through tests measuring the application of the portfolio learning model (independent variable) and students’ learning difficulties (dependent variable). The findings indicate that the Portfolio Learning Model was categorized as effective, as evidenced by the average score of 82.2 in the experimental class, with a standard deviation of 9.06. In contrast, the average score for learning difficulties was 51.67, with a standard deviation of 7.81. Hypothesis testing using the product moment correlation formula revealed that the calculated t-value (tcount = 0.06) was lower than the critical value (ttable = 0.245), leading to the acceptance of the alternative hypothesis. These results suggest a significant influence of the Portfolio Learning Model in reducing learning difficulties and improving academic performance among elementary school students.